Hull fouling as primary mechanism for the potential transport of non-indigenous species to Antarctica, Marion- and Gough Island - Melissa Boonzaaier (Zenodo, 2013)
Marine non-indigenous species (NIS) introductions are becoming more evident and marine ecosystems are threatened by this phenomenon. There are two main ship-based mechanisms for the transport of marine NIS, namely discharge of ballast water and hull fouling. To date, most research has focused on ballast water as the primary mechanism for propagule dispersal. In this study marine alien species that may potentially be transported primarily by hull fouling are investigated. Particularly, the focus lies on biological invasions in the Southern Ocean and the transport of propagules by the South African National Antarctic Programme supply vessel, the SA Agulhas. The vessel travels to and from three research bases: Antarctica, Marion- and Gough Island, with Cape Town Harbour as its main port. The SA Agulhas only transports cargo to the Antarctic region, suggesting that it has a consistent unidirectional flow of ballast water from Antarctica to Cape Town. Subsequently, this implies that propagule dispersal to the Antarctic and sub-Antarctic Islands would take place through hull fouling. The fouling biota found on the SA Agulhas include seven seaweed species and two marine faunal species. Furthermore, the invasive species occurring in Cape Town Harbour that may potentially invade the Antarctic region were also examined, namely Carcinus maenas, Ciona intestinalis, Diplosoma listerianum, Metridium senile, Mytilus galloprovincialis and Schimmelmannia elegans. The thermal tolerances of the common hull fouling biota found on the SA Agulhas vessel and invasive species occurring in Cape Town harbour were obtained by searching the primary literature. In addition, the sea surface temperatures (SSTs) from the three research bases in Antarctica, Marion- and Gough Island and of the study species’ distributions were obtained from the Smith-Reynolds Extended Sea Surface Temperatures (ERSST) dataset. The thermal tolerances and SST range, of each species, were used to compare with the SSTs of Antarctica and sub-Antarctic Islands. This ...